The progressiveness of the property tax as a communicative stimulus for respect for the social function of property - Lorenzon, Luiza Boff (Seven Editora, 2024)
This article sought, through an explanatory and exploratory study, to analyze the issue of the Urban Property Tax (IPTU) regarding the application of the progressive rate over time as an instrument of validation and social effectiveness, using for this purpose the theory of communicative action of Jürgen Habermas. Such an analysis is pertinent, insofar as Municipalities, many times, aiming to discourage the maintenance of urban properties, impose on owners the payment of IPTU at a different rate, which ends up generating the so-called collection character. To this end, an examination of Habermas’ theory of communicative action is followed, and then portrays and analyzes the progressive property tax over time. In the end, a relationship is made between the IPTU and the theory, in order to ascertain the foundations of this collection, analyzing mainly the effectiveness and social validation. DOI:https://doi.org/10.56238/sevened2024.007-028